High-Speed Interactive Thermo-Fluid Simulation by Using Reduced Order Models - IKEDA, Hiroshi; KOBAYASHI, Sachio; HASHIMA, Masayoshi; KOBAYASHI, Hiroki; SATO, Yuichi (Nihon Kikai Gakkai rombunshuu. C hen, 2012)
In this paper, we present a new thermo fluid simulation method by using reduced-order models, enabling large, real-time, detailed thermal flows with continuous user interaction. Our method is ideally suited for real-time simulation of high-resolution thermal fluid dynamics because our simulator is still fast even in the case of large problems expressed by using more than one million meshes. Our results indicate that one thousand times faster simulation can retain same level of accuracy as conventional methods. In addition, our method provides continuous user interaction in real-time. It allows that we can immediately assess how a thermal field changes when controlling air-conditioning equipment in a data center.